2023
DOI: 10.3390/app132413299
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermal Imaging Analysis in Screening for Toddler’s Fracture: A Proof-of-Concept Study

Reza Saatchi,
Shammi Ramlakhan

Abstract: This study explored and developed high-resolution infrared thermal (HRIT) imaging for screening toddler’s fractures. A toddler’s fracture is a common tibial fracture in children younger than six years old. The study included 39 participants admitted to an emergency department with a suspected toddler’s fracture. X-ray confirmed eight participants with a toddler’s fracture (20.5%). Infrared images of participants were recorded on their index visit, focusing on region-of-interests on the injured and the contrala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…This imbalance may bias the analysis and thus affect the accuracy of the results. A study reported a means to deal with this imbalance by using Euclidean distance between samples of the same category to reduce the associated imbalance [31].…”
Section: Convolutional Neural Network and Data Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This imbalance may bias the analysis and thus affect the accuracy of the results. A study reported a means to deal with this imbalance by using Euclidean distance between samples of the same category to reduce the associated imbalance [31].…”
Section: Convolutional Neural Network and Data Augmentationmentioning
confidence: 99%
“…A summary of other related studies using IRT imaging for medical diagnosis is provided in Table 1. Repetitive strain injuries 33 Wrist and hand Joints 0.65 [35] Fracture/sprain 133 Various 0.26 to 0.47 [31] Toddler's fracture 39 Tibia 1.1…”
Section: Infrared Thermal Imaging For Medical Diagnosismentioning
confidence: 99%